Strategi Pengembangan Program Pemberdayaan Usaha Mikro Dan Kecil Melalui Pembiayaan Usaha Syariah Di Kota Mojokerto - Risanda Alirastra Budiantoro; Pradipta Puspita Larasati; Sri Herianingrum (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
In business practices, micro and small businesses (SMEs) have several internal and external problems, such as difficulties in capital. These problems also occur in SMEs in Mojokerto. To solve this SME problem, several stakeholders in Mojokerto collaborated to create a Sharia Financing Program (Pusyar) on the basis of a Murabahah contract. The implementation of this program has been running for approximately five years, since the memorandum of understanding was signed by the Badan Amil Zakat Nasional Kota Mojokerto, PT. BPRS Kota Mojokerto, Dinas Koperasi Perindustrian dan Perdagangan (Diskoperindag) dan Masyarakat Ekonomi Syariah (MES) in 2013. During this time, the amount of budget allocation and realization, and the number of beneficiaries of the Pusyar program has increased, so basically the Pusyar financing program is needed by SMEs to survive the existing business competition. The renewal of this study, describes the Pusyar program model as a whole and formulates a development strategy by strengthening the roles and responsibilities of the stakeholders involved. Therefore, the aim of this study will be to examine more deeply in formulating the right development strategy of the SME empowerment program through the Pusyar financing program, so that the usefulness of this program can increase. The hope of the study result can be used as a reference for other local governments or the central government to apply this Pusyar program in the future.